Nutritive value improvement of seasonal legumes Vigna unguiculata, Canavalia ensiformis, Stizolobium niveum, Lablab purpureus, through processing their grains with Trichoderma viride M5-2. - Valiño, Elaine; Savón, Lourdes; Elías, A.; Rodríguez, Marleny; Albelo, Nereyda (Cuban Journal of Agricultural Science, 2016)
In order to improve the nutritive value of seasonal legumes through processing their grains with Trichoderma viride M5-2, several experiments were conducted at laboratory scale for producing inocula of this mutant cell, without adding nitrogen and minerals sources for different fermentation variants. Completely randomized designs with 4x6 and 4x2 factorial arrangement and three repetitions were used. Factors varied depending on the variant analysis. Factors were fermentation substrates (Vigna unguiculata, Canavalia ensiformis, Stizolobium niveum, and Lablab purpureus) and fermentation times (0, 24, 48, 72, 96 and 120 h). The experiments were conducted in erlenmeyer flasks of 500 mL with 10g of samples at 70% humidity. Samplings were conducted every 24 h to determine cellulolitic activity (endo β1-4 glucanase and exo β1-4 glucanase), mineral composition (Ca, Mg, P, K, ash), and bromatological composition (CP, TP, NDF, ADF, cellulose and lignin). The pH variation and humidity in each substrate were determined, as well as the amino acidic composition. The fermentation effectiveness was tested by infrared spectroscopy. Changes in the physico-chemical and mineral characteristics occurred in the legumes studied with remarkable increase of CP and TP, and a decrease of NDF. In the enzymatic kinetics, there was interaction in every factor (P< 00.1) for the four legumes. Maximum endo βD1-4 glucanase and exo βD1-4 glucanase values were reached in Vigna unguiculata, with 18.10 and 12.71 IU/mL at 72h and 24 h, respectively. The amino acidic pattern totally differed in content for the final fermented products. The analysis with infrared spectroscopy in Vigna unguiculata showed differences in bands intensity (1660-1100cm-1), due to fermentation. The strain T. viride M5-2 allowed the development of a biologically feasible fermentation process with meals of legume grains under study to improve its nutritional value, allowing the inclusion of these formulations on diets of monogastric animals. Furthermore, the results show the possibility of obtaining an inoculum without the addition of other nutrients in the medium, which is very important for the process of scaling. Keywords: seasonal legumes, Trichoderma viride, fermentation, fungi